2018
DOI: 10.2147/copd.s154012
|View full text |Cite
|
Sign up to set email alerts
|

Use of a 4-week up-titration regimen of roflumilast in patients with severe COPD

Abstract: BackgroundThe oral selective phosphodiesterase-4 inhibitor roflumilast (ROF) reduces exacerbations in patients with severe COPD. Adverse events (AEs) can cause early ROF discontinuation. Alternative dosing strategies may help patients continue their therapy.MethodsIn this multicenter, double-blind trial, 1,321 patients with severe COPD were randomized 1:1:1 to 4 weeks’ treatment with ROF 250 µg once daily (OD), 500 µg every other day (EOD), or 500 µg OD, each followed by ROF 500 µg OD for 8 weeks, plus standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 27 publications
(52 reference statements)
1
52
0
1
Order By: Relevance
“…The study took place between 10 July 2017 and 7 February 2018 in 47 study centres across six countries (Bulgaria [8], Czech Republic [2], Germany [16], Poland [13], Romania [7], and United Kingdom [1]). We recruited 616 patients, of whom 405 were eligible to be randomly assigned to medication, with 375 (93%) completing the study (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study took place between 10 July 2017 and 7 February 2018 in 47 study centres across six countries (Bulgaria [8], Czech Republic [2], Germany [16], Poland [13], Romania [7], and United Kingdom [1]). We recruited 616 patients, of whom 405 were eligible to be randomly assigned to medication, with 375 (93%) completing the study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with COPD, lung function and safety data had previously been obtained from up to 6 days treatment, although with no evaluation of symptoms [15]. Delivery of ensifentrine by inhalation aims to minimise the systemic adverse effects that have been associated with oral administration of PDE inhibitors [16].…”
Section: Introductionmentioning
confidence: 99%
“…In multivariate analysis, the OR for discontinuation with 500 μg was 2.87. Similar results were reported in a multicenter, double-blind trial [31]. COPD patients (n = 1,321) were randomly assigned to groups treated with roflumilast 250 μg once daily, 500 μg every other day, or 500 μg once daily for 4 weeks.…”
Section: Adverse Effectsmentioning
confidence: 56%
“… 26 28 Results from the OPTIMIZE study have confirmed this by demonstrating a 34% reduction in the odds of discontinuing therapy when an initial dose of roflumilast 250 μg OD is taken for 4 weeks before uptitration to 500 μg OD. 29 These strategies were not in effect at the time of DINO and DACOTA.…”
Section: Discussionmentioning
confidence: 99%